Konsumsi Pil KB Di Polindes Desa Kembangsari Kecamatan Jatibanteng Situbondo - Sari Priyanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
Women have difficulty in determining the contraceptivedevices. This is not only caused by unknown the limititation of available methods but also their unknown about requirement and safety of contraceptives methods.if contraceptives program are not successful,they will impact negatively towards other sectors.they are education,health,economic,adn etc.the aim of this study is to determine the obedient acceptors consuming pill contraceptives. Design of this study is a descriptive with survey.the variabel in this study is the obediens acceptors toward pill contraceptives.the Population in this study is 55 acceptors with a sample as many as 50 respondents. Sampling techniques used is the type of random probability sampling the study had been conducted in Kembangsari Jatibanteng Situbondo On July 12-18 years 2013.the data are collected by questionnaire sheets and processed by editing,coding, scoring, and tabulating.The results show that most respondents disobey consuming pill contraceptives as many as 29 respondents (58.0%) and a minority of respondents obey consuming pill contraceptives as many as 21 respondents (42.0%). In this study, many respondents disobey consuming pill contraceptives,so that they happen in conception due to disobey consuming pill contraceptives, and can cause them difficulty consuming 2 pills directly. Most of the obedient acceptors consuming pill contraceptives in Polindes Kembangsari, Jatibanteng Situbondo disobey consuming it. the health workers or midwives should provide counseling about the importance of consuming it regularly and the respondents are expected to add knowledge about the obedient acceptors consuming pill contraceptives by counselling heath about their obedient.